Georges Eekhoud en zijn werk - Van Puymbrouck, Herman (Antwerpen : De Nederlandsche Boekhandel, 1914)
Bibliotheek Jan Baghus
Met portret en handschrift.
Nederlands
Monografie
Keywords: Eekhoud, Georges